Earnings Announcements and the Components of the Bid-Ask Spread. - Krinsky, Itzhak; Lee, Jason (Journal of Finance, 1996)
This study investigates the behavior of the components of the bid-ask spread around earnings announcements. The authors find that the adverse selection cost component significantly increases surrounding the announcements, while the inventory holding and order processing components significantly decline during the same periods. Their results suggest that the directional change in the total bid-ask spread depends on the relative magnitudes of the changes in these three components. Specifically, the decreases in inventory holding costs and order processing costs imply that earnings announcements may have an insignificant impact on the total bid-ask spread, even when they result in increased information asymmetry.